Transformation from passive health to proactive prevention: research progress on glucose-lowering components and its mechanism of food and medicine homology resources - Li, Tianhao; Li, Jie; Sun, Yinfei; Liu, Dongqi; Liu, Juntao; Han, Jing; Chen, Xiaoyu; Kang, Wenyi (Frontiers in Nutrition, 2026)
Diabetes and its complications pose a threat to global human health. In the modern society, effectively preventing diabetes is a crucial means of safeguarding public well-being. Mounting evidence indicates that medicine-food homology foods possess significant medicinal and dietary value. However, these materials’ active compounds, and their structure–activity relationships on hypoglycemic function are unclear, this hinders the comprehensive utilization and development. In this review, 64 materials from 106 medicine-food homology foods claimed by the official possess a powerful hypoglycemic effects, according to statistics at the Web of Science, PubMed, and China National Knowledge Infrastructure (CNKI) databases. Current research indicates that these medicine-food homology foods contain Astrogali radius, Persicae semen, Menthae haplocalycis herba, Houttuyniae herba, etc. Terpenoids, flavonoids, alkaloids, phenylpropanoids, iridoids, and polysaccharides are regarded as their key bioactive compounds. This paper investigated and summried that the structure–activity relationships between these hypoglycemic constituents (triterpenoids, flavonoids, alkaloids, phenylpropanoid, iridoid and polysaccharide) and diabetes-related targets. In addition, this paper also reviews glucose-lowering mechanism of active compounds from medicine-food homology foods, including modulating digestive enzymes, regulating glucose metabolism (glucose absorption, gluconeogenesis and glycolysis), promoting insulin secretion, increasing insulin sensitivity, improving oxidative stress, reducing inflammatory response, promoting GLP-1 secretion and regulating gut microbiota. At the same time, the potential side effects of food with the same origin as medicine and food were discussed. Finally, the applications of medicine-food homology resources in glycemic management functional foods were reviewed. This provides a basis for the development of hypoglycemic functional food in the future, suggesting a shift in human health philosophy from treating existing diseases to preventing them, particularly for chronic metabolic diseases like diabetes.